Attraction, egg-laying preference and nymphal development of two vectors (Hemiptera: Aphrophoridae) of Xylella fastidiosa depending on the host plants - Bernat-Ponce, Saul; García-García, Rosalía; Aure, Cristina M.; Nieves-Carretero, Lorena; Monzó Ferrer, César; Bouvet, Juan Pedro; Beitia, Francisco José (Hellenic Entomological Society, 2024)
Póster de la presentación